Manejo integrado del psílido asiático (Diaphorina citri) en plantaciones de naranja (Citrus sinensis) - Tomalá Posligua, Alexis Isrrael (2020)
In our country, the development of orange cultivation has increased in recent years, being considered as a crop of vital importance for certain sectors of the Ecuadorian Coast. Being Caluma the main orange producing canton of the country, this being the official emblem of the city and sources of great ventures. In recent years, the growth of the Asian citrus psyllid (Diaphorina citri) has been diagnosed, whose direct damage is that it extracts large quantities and produces honey from the dew which favors the growth of sooty mold fungi. It is also the vector of the disease known as Huaglongbing, which is highly destructive for citrus fruits, which is caused by a bacterium of the genus Candidatus liberibacter. Knowing the severity of the Asian psyllid and the presence in neighboring countries, this study was in charge of evaluating the hypothesis that this insect has no greater relevance in our country, that is, it is found in low population quantities, which does not affect performance in terms of production is concerned.